Delayed inhibition in high trait anxiety athletes: Evidence from an event-related potential study - Watanabe, K.; Arii, T.; Sugo, T.; Tsuchiya, H. (Asian Journal of Sport and Exercise Psychology, 2025)
This study aimed to investigate the influence of trait anxiety on information processing in athletes, a topic that has yet to be examined thoroughly. We compared the information processing stages of individuals with high and low levels of trait anxiety using event-related potentials (ERPs). A total of 24 male collegiate athletes participated (age: 20.1 ± 1.3 years) in this study. ERPs (Go-N2, Go-P3, NoGo-N2, and NoGo-P3) were measured while participants performed the oddball task. The high trait anxiety group demonstrated delayed latency of NoGo-P3. However, reaction time was unaffected by trait anxiety. These findings indicate that athletes` trait anxiety affects neural information processing while leaving behavioral indicators, such as reaction time, unaffected. This insight has substantial implications for understanding the mechanisms by which trait anxiety contributes to performance deficits in athletes. Moreover, this study has the potential to inform new psychological support strategies to address performance impairments related to trait anxiety.